Músculo esquelético con acción muscular antogonista:Características metabólicas, contratiles y morfológicas - de Freitas, Carlos Eduardo A.; Freitas, Selma de Bastos Zambelli; Lopes, Francis da Silva; dal Pai-Silva, Maeli [UNESP]; Piçarro, Ivan da Cruz (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
The muscles can perform the same function in a specific segment (muscles of fast and slow contraction), and at the same time be antagonistic in relation to muscular action (flexors or extensors). The present research aimed to study the morphology, frequency and metabolism of fiber types and the contractile characteristics of extensor and flexors muscles of rabbit. We studied muscles anterior tibialis (AT), flexor digitorum supeficialis (FDS), extensor digitorum longus (EDL) and posterior tibialis (PT). The muscles were submitted to the techniques HE, NADH-TR and myofibrillar ATPase. In EDL and PT extensor muscles, the frequencies of red (SO + FOG) and white fibers (FG) were 68.77% and 31.23% versus 58.87% and 41.13%, respectively. In the AT and FDS flexor muscles, these frequencies were 75.14% and 24.86% versus 73.89% and 26.11%, respectively. In extensor muscles, the percentage of slow contraction fibers was 8.05% in EDL and 9.74% in PT, and in fast contraction, 91.95% in EDL and 90.26% in PT. In flexors, the slow contraction frequencies were 12.35% in AT and 8.17% in FDS, and in fast contraction, 87.65% and 91.83%, respectively. Skeletal muscles with antagonistic muscular actions (flexors and extensors) the morphological, contractile and metabolic characteristics are identical.
Skeletal muscles with antagonistic muscular actions: Morphological, contractile and metabolic characteristics
Keywords: Contractile ability; Metabolic; Morphologic; Skeletal muscle